My five moments of hand hygiene: A cross sectional questionnaire based study on adherence and barriers among nurses in central Kerala - S Madhumitha; Liya Mariam George; K S Meenakshi; Alphonsa Clara Vinson; Shaliet Rose Sebastian; Anoop Ivan Benjamin (Muller Journal of Medical Sciences and Research, 2023)
Background: Hospital acquired infections have remained a concern in the field of health care as a major cause of increasing morbidity, mortality and health care costs in healthcare facilities. In the present era of emerging and re-emerging infectious diseases and multidrug resistant pathogens, there is a growing emphasis on basic measures of prevention of infections, like maintaining good hand hygiene. Although The World Health Organization (WHO) has issued guidelines on hand washing procedure with an aim to reduce the prevalence of hospital associated infections, the compliance amongst health care workers is poor. Objective: To study the adherence and barriers relating to non-adherence to the five moments of hand hygiene among nursing staff in Central Kerala. Materials and Methods: The present cross sectional study was conducted among 360 female nurses using Snowball sampling technique. The quantitative data collected was analysed using the software SPSS version 20. Chi-square test was used for comparison of proportions across groups. Logistic regression analyses were used to find out the determinants of non-adherence. The qualitative data collected was analysed using thematic analysis and classified into themes and subthemes. Results: Out of 338 study participants, 304 (90%) reported to be adherent to the 5 moments of Hand Hygiene. The present study found that factors associated with hand hygiene behaviour among study participants were awareness about Hand Hygiene and educational qualification. Conclusion: The existing level of non-adherence can be a source for outbreak of hospital acquired infections in the community and hence needs to be addressed.